Outcomes of orbital decompression using surgical navigation in thyroid-associated ophthalmopathy. Issue 10 (October 2020) - Prevost, A.; Dekeister, C.; Caron, P.; Imbert, P.; Cavallier, Z.; Lauwers, F.; Boutault, F.
Abstract: Thyroid-associated ophthalmopathy can result in proptosis. In such cases, orbital decompression surgery is often warranted to reduce the adverse impact on patient quality of life. Due to the anatomical complexity of the orbit, navigation can be of considerable assistance during orbital decompression. The objective of this study was to evaluate the benefits of using a surgical navigation device in orbital decompression surgery. A retrospective study was performed based on patients who underwent decompression surgery with (N+) or without (N−) a navigation device between 1997 and 2017. Included patients had undergone unilateral or bilateral orbital decompression by resection of the orbital floor and medial wall of the orbit. Criteria assessed were the presence of debilitating postoperative diplopia, postoperative proptosis reduction, symmetry of protrusion of the eyeballs, and the duration of surgery. Three hundred and fifty eyes were analysed (191 patients): 205 in the N+ group and 145 in the N− group. Use of the surgical navigation system resulted in a greater proptosis reduction, and this result was statistically significant for the right eyeball ( P  = 0.03). The surgical navigation system had no effect on symmetry of protrusion of the eyeballs or on postoperative diplopia. Setting up the navigation device increased the duration of surgery by 40 minutes on average.